2004
DOI: 10.1128/mcb.24.8.3286-3294.2004
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of CNC Transcription Factors As Revealed by Gene Targeting of the Nrf3 Locus

Abstract: Cap'n'collar (CNC) family basic leucine zipper transcription factors play crucial roles in the regulation of mammalian gene expression and development. To determine the in vivo function of the CNC protein Nrf3 (NF-E2-related factor 3), we generated mice deficient in this transcription factor. We performed targeted disruption of two Nrf3 exons coding for CNC homology, basic DNA-binding, and leucine zipper dimerization domains. Nrf3 null mice developed normally and revealed no obvious phenotypic differences comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 64 publications
3
80
0
1
Order By: Relevance
“…Blockage of 80% Nrf1 expression by RNA interference diminished Nrf1 competition of ARE sites with other repressors (26), therefore abolishing AA induction of osterix expression and significantly impairing BMS cell differentiation and nodule information in vitro. Interestingly, it has been reported that disruption of Nrf1, but not Nrf2 or Nrf3, leads to embryonic lethality and causes anemia, a phenotype that is also seen in the sfx mutant mice, due to down-regulation of ␤-globin (35)(36)(37). In addition, although both Nrf1 and Nrf2 are expressed in the liver, only the liver-specific conditional knock-out of Nrf1 showed oxidative stress and impaired expression of various ARE-containing antioxidant genes, and developed liver cancer (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…Blockage of 80% Nrf1 expression by RNA interference diminished Nrf1 competition of ARE sites with other repressors (26), therefore abolishing AA induction of osterix expression and significantly impairing BMS cell differentiation and nodule information in vitro. Interestingly, it has been reported that disruption of Nrf1, but not Nrf2 or Nrf3, leads to embryonic lethality and causes anemia, a phenotype that is also seen in the sfx mutant mice, due to down-regulation of ␤-globin (35)(36)(37). In addition, although both Nrf1 and Nrf2 are expressed in the liver, only the liver-specific conditional knock-out of Nrf1 showed oxidative stress and impaired expression of various ARE-containing antioxidant genes, and developed liver cancer (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…The CNC domain, comprising a sequence of 43 conserved amino acids, is located N-terminally to the basic DNA-binding domain. The family members of the CNC domain heterodimerise with small Maf proteins (Derjuga et al 2004) and exhibit high homology in their DNA binding and leucine zipper domains; however, their biological functions are different. Most of the CNC family members are transcription activators, but Bach1 and Bach2 are transcription repressors.…”
Section: Nrf2 Transcription Factormentioning
confidence: 99%
“…The ARE-dependent HO-1 gene was significantly derepressed in bach1-null mutant mice, suggesting that HO-1 is negatively regulated by Bach1 (9). Although nrf3-null and bach2-null mutant mice have been reported (10,11), the contribution of these factors to AREmediated regulation is still to be determined.…”
mentioning
confidence: 98%